Students’ Obstacles in Determining Sense of Relation at English Department IAIN Langsa - Nanda Yuanita Windasari (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2021)
The aims of this research were to find out students’ obstacles in determining sense of relation at English Department of IAIN Langsa and also their efforts to solve the problems. The researcher used descriptive qualitative method and the data were collected by using documentation and semi-structured interview. The subject of this research were the 25 students of sixth semester of English Department selected purposively. The results of the study showed that the students had difficulties in determining the sense of relation, especially homonym, homophone and homograph. The students could not identify phonetic symbols of homophone in a text. They did not memorize and did not understand the definition of the three types of homonymy. Students were unable to analyze words because of the similarity, and they could not determine the words in listening. The efforts made by the students to understand the homonym, homophone and homograph include learning and increasing vocabulary through online dictionary, learning from the internet, and social media, learning with friends and asking lecturers about sense of relation particularly homonym, homophone, and homograph.